1998
DOI: 10.1121/1.421104
|View full text |Cite
|
Sign up to set email alerts
|

The role of vocal tract filtering in identity cueing in rhesus monkey (Macaca mulatta) vocalizations

Abstract: The importance of individual identity and kinship has been demonstrated in the social behavior of many nonhuman primates, with some evidence suggesting that individually distinctive acoustic features are present in their vocalizations as well. In order to systematically test whether acoustic cues to identity are reliably present across the vocal repertoire of rhesus monkeys (Macaca mulatta), we examined coos, grunts, and noisy screams produced by adult females of two free-ranging groups. First, acoustic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
173
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(185 citation statements)
references
References 21 publications
11
173
1
Order By: Relevance
“…In non-human primates, there is now ample evidence in several species that the laryngeal sound source is also subject to spectral patterning by the supralaryngeal vocal tract, resulting in formants clearly visible on sonograms (Owren et al 1997; figure 1). Thus, monkeys and apes use vocalizations that combine source due to vocal fold movement with filtering by vocal tract-comparable to our vowels (Rendall et al 1998). For example, baboon grunts are very similar to our neutral, central vowel pronounced with a relaxed vocal tract (Owren et al 1997).…”
Section: Human Voice and Primate Vocalizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In non-human primates, there is now ample evidence in several species that the laryngeal sound source is also subject to spectral patterning by the supralaryngeal vocal tract, resulting in formants clearly visible on sonograms (Owren et al 1997; figure 1). Thus, monkeys and apes use vocalizations that combine source due to vocal fold movement with filtering by vocal tract-comparable to our vowels (Rendall et al 1998). For example, baboon grunts are very similar to our neutral, central vowel pronounced with a relaxed vocal tract (Owren et al 1997).…”
Section: Human Voice and Primate Vocalizationsmentioning
confidence: 99%
“…Recent evidence for individual distinctiveness in vocalizations was obtained in the squirrel monkey (Boinski & Mitchell 1997), in the baboon (Owren et al 1997), the rhesus monkey (Rendall et al 1996(Rendall et al , 1998Owren & Rendall 2003), the Japanese macaque (Ceugniet & Izumi 2004a) and the cotton-top tamarin (Weiss et al 2001). Owren et al (1997) showed that the spectral energy peak (formant) patterning varied with caller identity in baboon grunts, and constituted the strongest grouping variable.…”
Section: Perception Of Identity Information In Voicementioning
confidence: 99%
See 2 more Smart Citations
“…1a. The open ellipses represent ranges for formant data for male (B_m) and female (B_f) chacma baboon grunts (redrawn from Owren et al, 1997;Rendall et al, 2004), and for human laughter (man: H_m, woman: H_f) (redrawn from Bachorowski and Owren, 2001), for rhesus monkey coo calls (R_c) and grunt calls (R_g) (estimated after data from Fitch 1997;Rendall et al, 1998) and for male Red Deer roars (D) (estimated after data from Fitch and Reby, 2001). The straight line, as in Fig.…”
Section: Radiographymentioning
confidence: 99%